An investigation of dynamic vehicle-bridge interaction effects based on a comprehensive set of trains and bridges. (15th March 2023) - Kohl, Antonia M.; Clement, Kim-Denise; Schneider, Jens; Firus, Andrei; Lombaert, Geert
Abstract: The consideration of interaction effects between vehicle and structure is an important aspect in the dynamic analysis of railway bridges. They usually lead to a reduction of the structural responses compared to computations without consideration of the vehicle-bridge interaction. The interaction effects can either be accounted for by Finite Element analysis including multi-body models of the vehicles or in a simplified way – as adopted by the actual regulations – by artificially increasing the bridge damping. In this way, a simplified dynamic analysis under consideration of the interaction effects is possible using the moving load model. However, several studies have shown that the current approach of the additional damping included in Eurocode 1 is non-conservative in many cases, possibly leading to an underestimation of the structural responses. The approach in Eurocode 1 as well as the more recently proposed approaches were based on a limited number of combinations of trains and bridges. In order to verify these approaches in a more thorough way, the present paper investigates the vehicle-bridge interaction effects based on 25 real high-speed passenger trains (including conventional and articulated trains) and over 100 single-span bridges with spans ranging from 5 m to 55 m. A typical criterion of analyzing the vehicle-bridge interaction phenomenon is the reduction of the structural acceleration computed using a 2D multi-body representation of the vehicle compared to the simplified moving load approach. Therefore, the reduction of the acceleration due to the interaction is discussed in detail and put in relation to the results of previous research. The results of over 800 000 dynamic analyses performed in the present study confirm that the additional damping approach depending on the bridge span as included in Eurocode 1 overestimates the actual vehicle-bridge interaction effects. Furthermore, the results show that recent additional damping approaches depending on bridge and train characteristics lead to more reliable additional damping values. Their application requires public availability of train characteristics and an extension of the approaches for articulated as well as heterogeneous trains. Highlights: Comprehensive collection of multi-body vehicle model characteristics. Computational series of over 800 000 train crossing calculations with and without interaction. Systematic analysis and critical discussion of different additional damping approaches.